The effect of curriculum change on the reading ability of English First Additional Language (EFAL) learners in grade ten : a case study - Rapetsoa, Johannah Mapotlakishe (My University, 2017)
Since 1998, the education system in South Africa has been changing from one curriculum to another, thereby affecting the quality of education. This was noted in the lowered standards of mathematics and science and in learners’ inability to read and write. The aim of this study was to investigate the effect of the changing curriculum on the reading ability of English First Additional Language (EFAL) learners in grade ten. Literature has revealed that reading efficiency determines the ability to cope with academic work load. Although Curriculum 2005 and the National Curriculum Statement were introduced to redress the apartheid education system, flaws were noted within these curricula, leading to the introduction of Curriculum and Assessment Policy Statement (CAPS) in 2012. A mixed method approach was adopted in this study. Both qualitative and quantitative methods were used to collect and analyse data. Case study design was used. Research techniques employed were interviews, observations, document review, questionnaires and standardised reading tests. Findings indicate that there are learners who fall behind with the attainment of reading skills required. On the other hand, curriculum change as a process, has a negative impact not only on the reading ability of learners, but also on the quality of education as well. Other factors that impact negatively on achievement of learners include, government’s political influence on the education system, flaws in the curricula, slow response of educators to curriculum change, and external factors affecting learners. Recommendations are that curriculum consumers, in particular educators and subject specialists should constantly refer to their policy documents to ensure that they are still working towards the learning outcomes stated. Again curriculum change should be treated as a process, where, along the way every consumer should be well-equipped for proper implementation. The government too should rethink the purpose of education and academic development of learners, and not only pursue political aspirations.
Thesis (Ph. D. (Language Education)) -- University of Limpopo, 2017.
Keywords: Curriculum change; Reading ability; English First Additional Language (EFAL); Grade 10 learners; Curriculum change -- South Africa; Reading (Secondary) -- South Africa.; English language -- Study and teaching (Secondary) -- South Africa.